O caso de corrupção dos gafanhotos (1998-2002) : o Executivo e o Legislativo em Roraima - Carvalho, Francisca Cleide Sousa (2019)
This dissertation aims to analyze the structure of the "locust" corruption scheme that occurred in the State of Roraima between 1998 and 2002, regarding the deviation of federal public resources from the payroll of State employees because of a political practice based on the phenomenon of patrimonialism. To do so, we will reflect on the history of national and regional politics beginning in 1980, in order to outline the continuity of the patrimonialism logic in Brazilian politics. We will seek to understand the alliance between the Executive and the Legislative in Roraima, as well as their articulation to divert the federal public funds and, with this, to know the aspects of patrimonialism demonstrated by the case of corruption of the "locust". Then, we will analyze the phenomenon of corruption under a conceptual patrimonial view, as one of the procedural of this phenomenon in the local political making, developed in the public space by elected representatives of the political system of Roraima. Seeking to perceive the overlap between private interest and public interest.